Efektivitas Aplikasi Sidoarjo Tanggap ‘Sigap’ dalam Penanggulangan Bencana di Kabupaten Sidoarjo - Fadia Dwi Nurdianty; Diana Hertati (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Sidoarjo Regency is one of the areas in East Java Province which has the potential for natural and non-natural disasters. So this disaster needs to be overcome with the role of the Sidoarjo Regency BPBD in efforts to deal with the impact of the disaster. So the Sidoarjo Regency BPBD created the Sidoarjo Response Application 'Sigap' which functions for the community if a disaster occurs or is affected by a disaster in the community. This research uses a qualitative method with a descriptive approach using primary and secondary data obtained through observation, interviews and documentation. The focus of this author's research is the effectiveness of the Sidoarjo Response 'Sigap' application in disaster management in Sidoarjo Regency. The results of this research explain that the Sidoarjo Regency BPBD has carried out its role in efforts to increase the effectiveness of the Sigap Application according to its duties and functions, namely: 1). System Quality 2). Information quality 3). Service Quality. There are obstacles or obstacles to research, namely the activities of village communities, but these obstacles can be minimized through the decision of the District BPBD. Sidoarjo. Supporting Factors are the involvement of all elements of Sidoarjo Regency society in participating in activities provided by agencies related to the Effectiveness of the Sigap Application in Disaster Management in Sidoarjo Regency.